DEVELOPMENT OF E-LEARNING MODULE FOR TECHNICAL DRAWING IN GRADE X OF BUILDING DESIGN AND INFORMATION MODELING VOCATIONAL COMPETENCY AT SMK NEGERI 5 PADANG - Nabila, Husna; Body, Revian (Jurnal Applied Science in Civil Engineering, 2023)
This research is motivated by the issue of not using modules in the technical drawing subject for Grade X in the Building Design and Information Modeling Vocational Competency at SMK Negeri 5 Padang. The aim of this research is to produce a valid and practical e-learning module product. The research method used is Research & Development (R&D) and follows the Decide, Design, Develop, and Evaluate (DDD-E) development model. Based on the research results, the percentages for material validity, media validity, and practicality tests are 95%, 86%, and 86%, respectively. The conclusion of this research is that the developed e-learning module is valid and practical for use in the technical drawing learning process for Grade X students in the Building Design and Information Modeling Vocational Competency at SMK Negeri 5 Padang.